Logística reversa como fator atenuante dos impactos causados ao meio ambiente: o caso das devoluções na empresa Mallory do grupo Taurus no Brasil - Stein, Sandra Luisa da Silva (2010)
This work deals with the contribution of reverse logistic to diminish the impacts caused to the environment caused by the permissive devolutions, of durable goods of consumption - today each time more dismissable - of the Brazilian electro-electronic sector. One searched to study forms to work the question of the devolutions being aimed at to reduce the number of solid residues in the environment and the decurrent ambient impacts of these devolutions. It rests on Logistic theoretical base in reverse and ambient responsibility. It is studied, initially, the importance, the benefits and the implications of reverse logistic, for after that presenting its evolution and processes. Its strategical objectives, the logistic cycle reverse and the logistic canals of distribution are presented reverse, with emphasis in the canals reverses of after-sell. A parallel between the reverse logistic and the Logistic Green becomes, presents evaluation on recycling, devolutions of products. In what it says respect to the ambient questions present evaluation on ambient conscience and ambient decorative clasp, of its beginning to the current moment. Also the question of the ambient responsibility and the conservation of the environment are studied. After that one searchs to bring these subjects for the particular case of the electro-electronic, sector and particularly for the case of the company Mallory of Grupo Taurus in Brazil. The carried through analysis showed that it also has lack of literature and of research and studies as for reverse logistic of after sell and particularly of the impacts of deriving goods of the electro-electronic sector. As result was gotten that the devolutions most of the time are made without criterion some and generate some social and ambient impacts in such a way, but with the focus in partnerships of manufacturers, retailers and the awareness of the consumers some improvements can be generated and be implanted as it was suggested in the research. One expects that this work serves as subsidy and incentive for other works that deal with the relation between Logistic of the Organizations, with objective in the reverse Logistic, Green Logistic and half-environment. In methodology terms, the research characterizes as theoretician-empiricist, of applied nature, with a predominantly qualitative boarding, of explore and not experimental character.